Evaluation of commercially available diagnostic tests for the detection of dengue virus NS1 antigen and anti-dengue virus IgM antibody. - Elizabeth A Hunsperger; Sutee Yoksan; Philippe Buchy; Vinh Chau Nguyen; Shamala Devi Sekaran; Delia A Enria; Susana Vazquez; Elizabeth Cartozian; Jose L Pelegrino; Harvey Artsob; Maria G Guzman; Piero Olliaro; et al. (PLoS Neglected Tropical Diseases)
Commercially available diagnostic test kits for detection of dengue virus (DENV) non-structural protein 1 (NS1) and anti-DENV IgM were evaluated for their sensitivity and specificity and other performance characteristics by a diagnostic laboratory network developed by World Health Organization (WHO), the UNICEF/UNDP/World Bank/WHO Special Programme for Research and Training in Tropical Diseases (TDR) and the Pediatric Dengue Vaccine Initiative (PDVI). Each network laboratory contributed characterized serum specimens for the panels used in the evaluation. Microplate enzyme-linked immunosorbent assay (ELISA) and rapid diagnostic test (RDT formats) were represented by the kits. Each ELISA was evaluated by 2 laboratories and RDTs were evaluated by at least 3 laboratories. The reference tests for IgM anti-DENV were laboratory developed assays produced by the Armed Forces Research Institute for Medical Science (AFRIMS) and the Centers for Disease Control and Prevention (CDC), and the NS1 reference test was reverse transcriptase polymerase chain reaction (RT-PCR). Results were analyzed to determine sensitivity, specificity, inter-laboratory and inter-reader agreement, lot-to-lot variation and ease-of-use. NS1 ELISA sensitivity was 60-75% and specificity 71-80%; NS1 RDT sensitivity was 38-71% and specificity 76-80%; the IgM anti-DENV RDTs sensitivity was 30-96%, with a specificity of 86-92%, and IgM anti-DENV ELISA sensitivity was 96-98% and specificity 78-91%. NS1 tests were generally more sensitive in specimens from the acute phase of dengue and in primary DENV infection, whereas IgM anti-DENV tests were less sensitive in secondary DENV infections. The reproducibility of the NS1 RDTs ranged from 92-99% and the IgM anti-DENV RDTs from 88-94%.